Comparative analysis of clinical characteristics of gout patients - Larisa Rotaru; Liliana Groppa; Eugeniu Russu; Svetlana Agachi; Larisa Spinei; Ludmila Negruța; Emil Ceban; Alexandru Corlateanu; Cristina Pamfil; Elena Sprincean; Cornelia Cornea (Folia Medica)
Aim: Given the documented rise in the incidence and prevalence of gout over the past decade, this study aims to comparatively assess patients of different ages affected by gout in Romania and the Republic of Moldova. Material and methods: This cross-sectional observational study selectively included 490 patients with gout treated in the Republic of Moldova and Romania Results: In Romania, the study included 15 women (6.1%) and 230 men (93.9%) (mean age 52.24±1.18 years). The mean age of gout onset in these patients was 42.5±0.89 years. In the Republic of Moldova, 26 women (10.6%) and 219 men (89.4%) were included (mean age 49.2±1.05 years), with mean age of gout onset 47.6±0.52 years. Of Romanian patients, 29 (11.8%) had chronic intermittent gout with a primary attack, 42 (17.2%) had repeated attacks, and 174 (71%) had chronic tophaceous gout. In the Republic of Moldova, there were 11 (4.5%) patients with chronic intermittent gout and a primary attack, 28 (11.5%) patients with repeated attacks, and 206 (84%) patients with chronic tophaceous gout. Hereditary predisposition was observed in six (2.5%) patients in Romania and nine (3.8%) patients in the Republic of Moldova, most frequently among family members such as fathers, brothers, and uncles. Conclusions: The study reveals similarities and differences between patient’s from Romania and the Republic of Moldova in terms of prevalence, clinical evolution and hereditary predisposition of gout, underlining the need for a tailor-made approach in the management of this disease.